Transparency and Accountability in Public Services and Policies in Administrative Law: A Comparative Study of Indonesia and Norway - Prasetyo Isbandono; Dian Arlupi Utami; Agus Prastyawan; Gading Gamaputra; Yuni Lestari (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
This study aims to compare the application of transparency and accountability principles in public services and policies between Indonesia and Norway within the context of administrative law, as well as to identify the supporting and inhibiting factors affecting their implementation in both countries. The research employs a normative legal method with statutory, comparative, and conceptual approaches to analyze regulations, legal doctrines, and administrative practices related to transparency and accountability in Indonesia and Norway through literature studies and qualitative analysis. The findings reveal significant differences in the implementation of transparency and accountability principles in administrative law between the two countries, both in regulations and practice. Norway has successfully built a transparent and accountable public administration system through strong regulations, independent oversight, and a legal culture that supports information openness and public official accountability. On the other hand, although Indonesia has enacted various regulations, such as the Public Information Disclosure Act and several oversight institutions, implementation still faces numerous challenges, including a lack of transparency in bureaucracy, low public awareness, and persistent corruption. The key factors supporting transparency and accountability effectiveness in Norway include a robust oversight system, digitalization of public services, and high levels of press freedom and public participation. Meanwhile, in Indonesia, the main challenges lie in weak law enforcement, political interference, and inconsistencies in implementing openness and accountability policies